Ocular Surface Microbiota in Contact Lens Users and Contact-Lens-Associated Bacterial Keratitis - Jasmine Andersson; Josef K. Vogt; Marlene D. Dalgaard; Oluf Pedersen; Kim Holmgaard; Steffen Heegaard (Vision, 2021)
Our objectives were to investigate whether the conjunctival microbiota is altered by contact lens wear and/or bacterial keratitis and to explore the hypothesis that commensals of conjunctival microbiota contribute to bacterial keratitis. Swab samples from both eyes were collected separately from the inferior fornix of the conjunctiva of non-contact-lens users (nparticipants = 28) and contact lens users (nparticipants = 26) and from patients with contact-lens-associated bacterial keratitis (nparticipants = 9). DNA from conjunctival swab samples was analyzed with 16S rRNA gene amplicon sequencing. Pathogens from the corneal infiltrates were identified by cultivation. In total, we identified 19 phyla and 283 genera; the four most abundant genera were Pseudomonas, Enhydrobacter, Staphylococcus, and Cutibacterium. Several pathogens related to bacterial keratitis were identified in the conjunctival microbiota of the whole study population, and the same bacteria were identified by both methods in the conjunctiva and cornea for four patients with contact-lens-associated bacterial keratitis. The overall conjunctival microbiota profile was not altered by contact lens wear or bacterial keratitis; thus, it does not appear to contribute to the development of bacterial keratitis in contact lens users. However, in some individuals, conjunctival microbiota may harbor opportunistic pathogens causing contact-lens-associated bacterial keratitis.